The Impact of Market Revitalization on Community Satisfaction and Trader Welfare (A Study on Paya Dua Market, North Aceh Regency) - Abrar, Muhammad; Isnawati, Putri (Yayasan Rahmat Islamiyah, 2025)
Traditional markets play a strategic role in both local and national economies, serving not only as centers of economic transactions but also as spaces for social interaction and cultural preservation. This study analyzes the impact of the revitalization of Paya Dua Market, located in Banda Baro Subdistrict, North Aceh Regency, on community satisfaction and traders’ welfare. Employing a quantitative approach, the study involved 92 community members and 52 traders selected using accidental sampling techniques. Data were collected through structured questionnaires. The analysis results indicate that market revitalization has a positive and significant effect on community satisfaction (t = 3.509; p = 0.003), but no significant effect on traders’ welfare (t = -0.477; p = 0.682). Market revitalization contributed 68.2% to community satisfaction, whereas it accounted for only 0.13% of the variance in traders’ welfare, with the remainder influenced by other factors outside the scope of this research model.